Phenolics over Zeolites and Related Materials—Biomedical and Environmental Applications - Bojana Nedić Vasiljević; Marija Takić; Nataša R. Mijailović; Aleksandra Janošević Ležaić; Anka Jevremović; Snežana Uskoković-Marković; Maja Milojević-Rakić; Danica Bajuk-Bogdanović (Antioxidants)
This work analyzes the following two aspects of zeolite applications: their application as carriers in delivery systems for phenolics applied as antioxidants or anticancer agents and the efficient removal of phenolic compounds from aqueous environments. The dual role of zeolites in increasing antioxidant bioavailability and environmental remediation is summarized, and perspectives on progress in zeolite adaptable applications are given. Special attention is given to theoretical methods that will guide future advanced delivery systems for biomedical applications, as well as serve as a focal point in designing multipurpose materials for comprehensive environmental solutions. Perspectives in both fields are discussed.